The Dampak Sosialisasi Mitigasi Bencana Gempa Bumi dan Tsunami Bagi Guru dan Siswa SMAN Bina Insani, Tangerang Banten - Afiat Anugrahadi; Yusraida Khairani Dalimunthe; Agus Guntoro Guntoro; Masagus Ahmad Azizi; Amalia Yunita Puteri; Sona Agustin (LPPM Institut Teknologi Petroleum Balongan, 2023)
Implementation of Community Service (PKM) themed Socialization of Earthquake and Tsunami Disaster Mitigation for Teachers and Students of SMAN Bina Insani, Tangerang Banten has been carried out. The purpose of this activity is to find out the impact of socialization which is carried out based on the Likert scale. The method used in this research is to provide a pre-socialization questionnaire to see the respondents' initial knowledge regarding the earthquake and tsunami disaster, then proceed with the presentation of material related to the earthquake and tsunami disaster through zoom and finally given another socialization questionnaire to see the extent of the benefits from this socialization. So based on the socialization questionnaire, the results showed that 39% of respondents often heard about earthquakes; 57% of respondents never find out the causes of earthquakes; 63% of respondents rarely find out about the mechanisms of damage caused by earthquakes; 53% of respondents never find out about tips and handling in case of an earthquake nearby; 61% of respondents rarely heard about the tsunami; 61% of respondents never found out the cause of the tsunami; 63% of respondents rarely hear tsunami early warnings; 64% of respondents rarely find out tips for handling if a tsunami occurs nearby. and after the socialization was held it was found that 96% of respondents felt that this socialization activity was very useful to increase their knowledge regarding earthquakes and 97% of respondents felt that this socialization activity was very useful to increase their knowledge regarding the tsunami.